Talk dirty to me! Sexblogging som performativ intervention og medieret tilblivelse - Marie Løntoft (The Royal Danish Library, 2015)
In July 2011 an anonymous blogger began posting small, catchy stories from her personal sex life on Tumblr. Her blog, 'Sugar Tits', soon developed into a community og young followers posting all kinds of sex related questions, comments and photos of their own bodies. In this article I analyse the 'sex blog' as a digital media as well as 'sex blogging' as a performative practise crossing the divide between offline and online. By focusing on the interactive and participative aspects of 'Sugar Tits' my aim is to trace connections between the digital media of the blog and the materiality of the sexed and sexualised body: How does the formal structure and interactive functions of 'Sugar Tits' construct the body? And how does this collective, online mediation of the intimate body interfere with the offline bodies and desires of the participating followers? These questions are addressed within a framework of theories of performance and performativity as well as poststructualist feminist thinking concerning the materiality of the body. In the end I consider the feminist potential of the sexual 'blog body' suggesting that 'Sugar Tits' may be considered a feminist figuration of collective subjectivity.